DEPLETION OF LYSYL OXIDASE-LIKE 4 (LOXL4) ATTENUATES COLONY FORMATION IN VITRO AND COLLAGEN DEPOSITION IN VIVO BREAST CANCER MODEL - Ni Luh Gede Yoni Komalasari; I Gde Haryo Ganesha; I Gusti Nyoman Sri Wiryawan; Nahoko Tomonobu; Masakiyo Sakaguchi (Universitas Airlangga, Surabaya, Indonesia, 2024)
Highlights Revealing LOX family members' mechanisms in promoting invasive breast cancer progression is essential for targeting specific molecules in invasive breast cancer. Depletion of LOXL4 in invasive breast cancer shows attenuation of cell invasiveness in vitro and collagen deposition in tumor models in vivo. Abstract Background: Lysyl oxidase (LOX) family proteins have recently become a topic in cancer progression. Our recent study found a high expression of LOX-like 4 (LOXL4) in MDA-MB-231 cells. Objective: To reveal the impact of depleted LOXL4 in both in vitro and in vivo breast cancer models from a histological perspective. Material and Method: Endogenous LOXL4 was depleted using the CRISPR/Cas9 on MDA-MB-231 parental cells. Based on the LOXL4 protein expression, the clone was determined for the next experiment, thus generating MDA-MB-231 LOXL4 KO. Cell assay was conducted using colony formation assay (n=3) followed by crystal violet staining. The indicated cells were inoculated orthotopically to female BALB/c nude mice (n=5). At the end of the experiment, tumors were isolated, fixed, and prepared for Masson Trichrome staining. Result: CRISPR/Cas9 completely depleted LOXL4 expression on clone number #2-22. Depletion of LOXL4 reduced the colony size formed by MDA-MB-231 cells. MDA-MB-231 LOXL4 KO #2-22 derived tumors showed depressed tumor volume compared to the parental group. Reduced collagen was also observed from the Masson Trichrome staining (p<0.001). Conclusion: Depletion of LOXL4 downregulates the growth of MDA-MB-231 cells in vitro and collagen deposition in vivo.